PENINGKATAN HASIL BELAJAR MENGGUNAKAN METODE SIMULASI DALAM PEMBELAJARAN PKn DI KELAS VI SEKOLAH DASAR - Dudung, Dudung; Salimi, Asmayani; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve the performance of teachers through the ability of teachers in designing and implementing learning is characterized by the success of teachers in improving student learning outcomes. This research was conducted in class VI SD Negeri 04 Kinande Bengkayang with the number of students 12 male students and 8 female students. This research is collaborative, using descriptive method, and with form of action research class (PTK). Data collection techniques used are direct observation techniques, and measurement techniques with data collection tool that is the observation sheet. Based on the results of the research, the results obtained IPKG I cycle I with an average score of 3.58 with good category and on the second cycle average score 3.60 with very good category, an increase of 0.02. Assessment of the results obtained from IPKG II obtained the average score in the first cycle that is equal to 3.54 with good category and on the second cycle average score 3.62 with very good category, and increased by 0.08. Based on the data analysis of student learning outcomes in the form of evaluation in cycle I obtained an average value of 59.5 with sufficient category and in cycle II obtained an average value of 89.5 with a very good category that increased by 30.00. Keywords: Improvement, Learning Outcomes, Simulation Methods, Citizenship   Education.